The rostroventral part of the thalamic reticular nucleus modulates fear extinction - Joon-Hyuk Lee (Nature Portfolio, 2019)
The precise role of the thalamic reticular nucleus in fear is not understood. Here, the authors report that the rostroventral part of the reticular nucleus is involved in the extinction of tone conditioned fear memory through its inhibitory projections to the dorsal midline thalamus.